Implementasi Model Pelayanan Pendidikan Inklusif bagi Anak Berkebutuhan Khusus (ABK) di SD Al Firdaus Surakarta: Jurnal Pendidikan Inklusif - Khoqifah, Rena; Sunardi, Sunardi; Martika, Tias (Jurusan Pendidikan Luar Biasa, 2024)
The purpose of this research is to understand how the implementation of an inclusive education service model for children with special needs (ABK) is carried out at Al Firdaus Elementary School in Surakarta. The method used in this research is a qualitative case study method. The subjects of this research are the School Principal, the Inclusion Team, and Special Guidance Teachers. (SPECIAL EDUCATION TEACHER). Data collection in this research was conducted through interviews with the Principal, the Inclusion Team, and Special Guidance Teachers. (SPECIAL EDUCATION TEACHER). In addition, an analysis of supporting research documents was also conducted. The technique for testing the validity of data uses data source triangulation. The data analysis technique in this research employs data reduction, data presentation, and conclusion drawing in accordance with the theory of Miles and Huberman. The research findings concluded that Al Firdaus Elementary School employs an inclusive education service model that combines both regular (full inclusion) and pull-out approaches. Furthermore, the learning process for students with special needs at Al Firdaus Elementary School consists of two types: one where students require modifications in terms of materials, targets, worksheets, and assessment systems, and another where students who do not need modifications have the same materials, targets, worksheets, and assessment systems as their regular classmates. In its implementation, the school has applied principles that must be understood in organizing inclusive education services, namely friendly education, optimal development, collaboration with relevant parties, and system change.